The Quality of Analysts Earnings Forecasts During the Asian Crisis: Evidence from Singapore - LOH, Roger (Institutional Knowledge at Singapore Management University, 2003)
Examines the efficiency of security analysts' earnings forecasts in Singapore. Regression of actual earnings change on forecasted change; Extremism in forecasted change; Impact of business crisis on the quality of earnings forecasts.